Characterization of the complete chloroplast genome of Tilia taishanensis S. B. Liang (Tiliaceae). Issue 3 (2nd July 2020) - Lu, Yi-Zeng; Li, Wen-Qing; Wang, Ning; Wang, Yan; Han, Yi; Sun, Tao; Liu, Li-Jiang; Xie, Xiao-Man; Wang, Yin-Hua
Abstract: The complete chloroplast genome of an endangered endemic species in China Tilia taishanensis was sequenced with Illumina HiSeq 2000 platform. It was a typical quadruple structure as other plants of Tilia with 162, 803 bp in length, including a large single copy (LSC: 91, 114 bp) region and a small single copy (SSC: 20, 379 bp) which were separated by a pair of inverted repeats (IRa, b: 25, 655 bp) region. The overall GC content is 36.5%. A total of 129 genes was annotated which contained 84 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. ML Phylogenetic analysis compared with 33 expressed chloroplast genomes revealed that T. taishanensis was a sister to other Tilia species.